TGF‐β1–p53 cooperativity regulates a profibrotic genomic program in the kidney: molecular mechanisms and clinical implications. Issue 10 (6th July 2019) - Higgins, Craig E.; Tang, Jiaqi; Mian, Badar M.; Higgins, Stephen P.; Gifford, Cody C.; Conti, David J.; Meldrum, Kirstan K.; Samarakoon, Rohan; Higgins, Paul J.
ABSTRACT: Chronic kidney disease affects >15% of the U.S. population and >850 million individuals worldwide. Fibrosis is the common outcome of many chronic renal disorders and, although the etiology varies ( i.e ., diabetes, hypertension, ischemia, acute injury, and urologic obstructive disorders), persistently elevated renal TGF‐β1 levels result in the relentless progression of fibrotic disease. TGF‐β1 orchestrates the multifaceted program of renal fibrogenesis involving proximal tubular dysfunction, failed epithelial recovery and redifferentiation, and subsequent tubulointerstitial fibrosis, eventually leading to chronic renal disease. Recent findings implicate p53 as a cofactor in the TGF‐β1‐induced signaling pathway and a transcriptional coregulator of several TGF‐β1 profibrotic response genes by complexing with receptor‐activated SMADs, which are homologous to the small worms (SMA) and Drosophilia mothers against decapentaplegic (MAD) gene families. The cooperative p53‐TGF‐β1 genomic cluster includes genes involved in cell growth control and extracellular matrix remodeling [ e.g., plasminogen activator inhibitor‐1 (PAI‐1; serine protease inhibitor, clade E, member 1), connective tissue growth factor, and collagen I]. Although the molecular basis for this codependency is unclear, many TGF‐β1‐responsive genes possess p53 binding motifs. p53 up‐regulation and increased p53 phosphorylation; moreover, they are evident in nephrotoxin‐ and ischemia/reperfusion‐induced injury, diabetic nephropathy, ureteral obstructive disease, and kidney allograft rejection. Pharmacologic and genetic approaches that target p53 attenuate expression of the involved genes and mitigate the fibrotic response, confirming a key role for p53 in renal disorders. This review focuses on mechanisms whereby p53 functions as a transcriptional regulator within the TGF‐β1 cluster with an emphasis on the potent fibrosis‐promoting PAI‐1 gene.—Higgins, C. E., Tang, J., Mian, B. M., Higgins, S. P., Gifford, C. C., Conti, D. J., Meldrum, K. K., Samarakoon, R., Higgins, P. J. TGF‐β1‐p53 cooperativity regulates a profibrotic genomic program in the kidney: molecular mechanisms and clinical implications. FASEB J. 33, 10596–10606 (2019). www.fasebj.org